Drunkenness, Tattoos, and Dirty Underwear: Jeremiah as a Modern Masculine Metaphor - Carvalho, Corrine (The catholic biblical quarterly, 2018)
Jeremiah's body functions as a canvas in the book on which loss of patriarchal privilege due to colonization plays out. This article looks at three tropes of masculinity in the book: drunkenness, bodily markings, and gendered prophetic performance to explore how the text uses metaphoric images to represent this rhetorical strategy. The article relates these tropes to gender performances by contemporary white males who also negotiate loss of patriarchal privilege.